Assessment of in ovo soursop (Annona muricata L.) leaf extract injection on intestinal microbes in Noiler chicks - Timothy T. Kuka; Simplice D. Karou; Anani Kokou; Batomayena Bakoma (The Microbe)
Soursop leaves possess valuable phytochemicals that can improve the health performance of chickens leading to production efficiency. This study was designed to assess the effect of in ovo injection of soursop leaf extract (SLE) on the intestinal microbes of Noiler chicks. A total of 640 incubated fertile eggs were randomly distributed into four groups: 0.25 µg SLE, 0.5 µg SLE, 0.75 µg/ml SLE, and a non-injected control group on day 18 of incubation. Each of the three treatment groups received 0.2 ml of SLE injected into the airspace of the eggs. Hatched chicks from the groups were divided into four replicates and reared in a completely randomized design. At ten days of age, two chicks per replicate were sacrificed, caeca contents of the chicks were collected aseptically and used for microbial enumeration following standard microbial procedures and specific agars. Data collected was subjected to analysis of variance and means were compared using Tukey’s HSD at p ≤ 0.05. Results showed that E. coli count was significantly lower (p < 0.05) in the group with the highest concentration of SLE, this is due to the antibacterial activities of soursop leaf extract. It was concluded that in ovo injection of SLE at 0.75 µg confers intestinal health by reducing caeca E. coli count in Noiler chicks.